Variasi Tegangan Pompa Terhadap Kinerja Mesin Sepeda Motor Honda Scoopy - Muliawan, Arief; Ramadhan, Muhammad Derian Alfaraldi; Anoi, Yano Hurung (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2022)
In this study, the effect of pump voltage on engine performance and fuel consumption on the Honda Scoopy motorbike was investigated. The voltage value is between 5 volts and 7 volts for the fuel pump pump pressure. Based on the results of the influence of variations in the voltage electrical fuel pump on engine performance on Honda Scoopy motorcycles by looking for some data, namely; Voltage supplied to the fuel pump, engine RPM, and fuel consumption. From some of the data above, results with the following values are obtained; The voltage values used are 5.80 V, 6.54 V, 7.34 V, 6.68 V, and 7.10 V. The RPM values obtained are 1200, 2607, 3289, 2802 and 3210. The pressure values at the fuel pump obtained are 20 Psi, 21.5 Psi, 27.5 Psi, 22.5 Psi and 25 Psi with an average fuel consumption value of 12 ml/minute for all variables. The results of the study show that the pressure on the fuel is affected by the voltage which affects the engine rpm. Furthermore, the voltage does not affect the value of fuel consumption on the machine.